The Use of Multimodal Strategies to Develop Vocabulary and Reading Comprehension: A Bibliometric Analysis - Lopez, Carolyn Marie S.; Mangulad, Mildred P.; Santos, Joseline M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
A bibliometric analysis was used to explore studies regarding the development of students’ vocabulary and reading comprehension with the use of multimodal strategies. There are 1,290 Scopus- indexed articles from 2020 to 2024, with key authors, theories, and themes identified. The results show increased exploration and interest in gamification, augmented reality, and digital tools developed and analyzed using theories in cognition and motivation. This study identifies the trends and gaps in future research and practice. Specifically, this study highlights that more longitudinal studies are needed, as well as more research on how multimodal learning connects with digital and media literacy.